URGENSI KETERAMPILAN LITERASI KEUANGAN SEJAK DINI: ANALISIS KENDALA DAN PROSPEK - Rina Apriliani (Prosiding Seminar Nasional Indonesia, 2023)
This qualitative research examines the importance and urgency of developing financial literacy skills from an early age. Financial literacy skills are important for individuals to be able to make informed financial decisions. However, research shows that many individuals need to acquire these skills, which can lead to financial hardship and poor decision making. This research explores the obstacles and prospects for developing financial literacy skills from an early age. This research is based on a qualitative methodology, using semi-structured interviews with parents, teachers and experts in the field of financial literacy. This research also includes a literature review on financial literacy. Findings show a great need for financial literacy education from an early age, as parents and teachers recognize the importance of this skill. However, there are many obstacles to providing financial literacy education, including the need for more resources, curriculum limitations, and limited training for teachers. Despite these challenges, there are prospects for improving financial literacy education, including integrating financial literacy into existing curricula, offering professional development for teachers, and providing resources for parents to educate their children at home. Overall, this research highlights the importance of financial literacy skills and the urgency of developing them from an early age. This research provides insight into the obstacles and prospects for financial literacy education, which can inform policies and initiatives to improve financial literacy for future generations.